Urgent ERCP with pancreatic stent placement or replacement for salvage of post-ERCP pancreatitis - Kerdsirichairat, Tossapol; Attam, Rajeev; Arain, Mustafa; Bakman, Yan; Radosevich, David; Freeman, Martin (Endoscopy, 2014)
Background and study aims: Urgent placement or replacement of pancreatic stents shortly after endoscopic retrograde cholangiopancreatography (ERCP) might attenuate the course of evolving post-ERCP pancreatitis (PEP).Patients and methods: Salvage ERCP with de novo pancreatic stent placement or replacement of outwardly migrated stents was performed within 2 – 48 hours in patients with evolving PEP accompanied by severe pain, systemic inflammatory response syndrome (SIRS), and major elevations in serum amylase and lipase. Serial pain scores, amylase and lipase levels, and hospital course were studied.Results: PEP according to Cotton consensus criteria developed after 64 (2 %) of 3216 ERCPs over 3 years. Of the 64 patients with PEP, 14 underwent salvage ERCP (5 without and 9 with prior pancreatic stents, 7 of which had migrated outwards prematurely). All patients had SIRS and a high score (≥ 3) for the bedside index for severity in acute pancreatitis. Median clinical onset of PEP was at 5 hours (range 0 – 68 hours) in patients with prophylactic pancreatic stents vs. 2 hours (range 0.5 – 2.5 hours) in patients without prophylactic pancreatic stents (P < 0.05). Salvage ERCP was performed at a median of 10 hours (interquartile range [IQR] 2.4 – 22.7 hours). Improvement in pain, amylase, lipase, and resolution of SIRS were statistically significant at 24 hours after salvage ERCP (P = 0.003). Median length of hospital stay was 2 days (IQR 1 – 4.75). No necrotizing pancreatitis or late complications occurred.Conclusion: Urgent salvage ERCP with de novo pancreatic stent placement or replacement of a migrated stent is a novel approach in the setting of early PEP, and was associated with rapid resolution of clinical pancreatitis and reduction in levels of amylase and lipase.